Case Report: Patent ductus arteriosus with tuberous sclerosis complex - Chen, Tingrui; Wu, Xiaoxiao; Wang, Yiping (Frontiers in Cardiovascular Medicine, 2024)
A 33-year-old patient presented with a chief complaint of patent ductus arteriosus (PDA) persisting for over 30 years. Physical examination revealed bilateral facial angiofibromas, multiple nail fibromas, intraoral fibromas, and a ’shagreen patch’ on the left lumbar region. Genetic testing was performed using a peripheral venous blood sample, which confirmed the diagnosis of Tuberous Sclerosis Type 2 (TSC2). Subsequently, the patient underwent cardiac color Doppler ultrasound and chest computed tomography angiography, which confirmed the presence of PDA. Tuberous sclerosis complex (TSC) is associated with cardiovascular diseases. The initial clinical manifestation of TSC is usually cardiac rhabdomyoma in children, and it is rarely reported in adults with PDA. In this case, the patient was diagnosed with PDA when he was young, and the genetic test showed heterozygous variation of TSC2 gene. The purpose of this article is to explore the correlation between TSC and PDA at the gene level through literature review.